Returns to Higher Education in China: Evidence from the 1999 Higher Education Expansion Using Fuzzy Regression Discontinuity - Fengyan Dai; Fang Cai; Yu Zhu (Institute of Labor Economics (IZA), 2018)
China experienced a 47% expansion in higher education enrolment between 1998 and 1999, and a six-fold expansion in the decade to 2008. In this paper, we explore a fuzzy discontinuity in the months of births induced by the expansion to study the returns to higher education in China. We find that the mean years of education increased by roughly one full year around the cut-off point of the 1999 expansion as defined by months of births. Importantly, each additional year of university education induced by the 1999 higher education expansion increases monthly wage income by 21%, whereas the corresponding OLS estimate is only 8%. Our findings are insensitive to alternative window widths, functional forms, or the exclusion of the self-employed. Moreover, the returns to degrees also appear to vary by gender, with lowers returns to women except when they are the only child in the family.
Keywords: I23; I26; 330; returns to higher education; higher education expansion; regression discontinuity design; China